Fungsi Prefiks me-(N) dalam Cerita Populer Berjudul Antagonist Princess - Zulfa, Ilma (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2025)
The addition of the prefix me-N to a word does not only mean doing something. However, this addition has various grammatical meanings. The objectives of this research are (1) to describe the affixation of prefix me-N, (2) the function of prefix me-N as derivational or inflectional, and (3) the grammatical meaning of prefix me-N in the Antagonist Princess story. The data in this research are the prefix me-N in the popular story,